Agrophysical properties of soil in seed layer before sowing of spring crops - Borodin, A.L. (AgroChemistry and Soil Science, 2016)
Agrophysical properties of the dark gray podzolic heavy-loamy soil and typical heavy-loamy chernozem within the seed layer (structural composition, bulk density, moisture content) in the spring before sowing of spring crops in 2013-2015 were investigated. It was determined that agrophysical properties of dark gray podzolic soil formed within seed layer as a result of traditional presowing tillage were different from the assumed ones (according to current agronomical requirements): there were lumps in sowing layer, content of aggregates of agronomically useful size was significantly smaller than the permissible; bulk density of the seed layer was too high. Good moisture reserves formed during the autumn and winter period. Parameters of chernozem typical structure before barley sowing in 2014 were acceptable except the lumps presence of sowing layer. Tillage by experimental tool formed better structure of over-seed layer than traditional cultivation.